The diversity of newly discovered deterioration patterns in ancient Egyptian pigments: consequences to entirely new restoration strategies and to the Egyptological colour symbolism - Schiegl, Solveig; Weiner, Karl Ludwig; El Goresy, Ahmed (MRS online proceedings library, 1992)
Polished cross sections through more than 1000 pigment samples from ancient Egyptian monuments (5th Dynasty to Roman Times) were investigated in reflected light, with SEM, and with electron microprobe techniques (EMPA). These combined analytical techniques allow many insights into the painting layers and down to the substrate. Textural relations of both the primary paintings and of the deterioration products can then be delineated. They also discern the stages of the various deterioration processes and the degree of damage of the painting layers.